1973
DOI: 10.1159/000245472
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Osteoporosis in Hemiplegia

Abstract: A study of bone loss in the paretic hand of hemiplegic patients shows that there is a progressive osteoporosis which does not appear to be influenced by changes in muscle power short of full recovery, but which is strongly correlated with the duration of the stroke. Consequently, hemiplegic patients are increasingly at risk from fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
5

Year Published

1976
1976
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 2 publications
0
2
0
5
Order By: Relevance
“…Losses of cortical bone in man are seen in immobilization [1][2][3] and in senile osteoporosis [4,5]. Studies in our laboratory have also shown characteristic losses of tibial cortical bone in restrained hypodynamic monkeys [6].…”
Section: Methodsmentioning
confidence: 92%
“…Losses of cortical bone in man are seen in immobilization [1][2][3] and in senile osteoporosis [4,5]. Studies in our laboratory have also shown characteristic losses of tibial cortical bone in restrained hypodynamic monkeys [6].…”
Section: Methodsmentioning
confidence: 92%
“…İnme sonrası ortaya çıkan komplikasyonlar arasında yer alan osteoporozun, kırık riskini genel popülasyona göre 2-4 kat daha fazla arttırdığı bildirildiğinden oldukça önem-li ancak bir o kadar da gözden kaçırılabilen bir durumdur (2)(3)(4)(5). Patogenezi net olarak bilinmese de genel ve lokal immobilizasyon başta olmak üzere ilerlemiş yaş, cinsiyet, spastisite şiddeti, kas atrofisi ile ilişkili olduğu bildirilmektedir (6,7).…”
Section: Introductionunclassified
“…It has been well documented that wasting of muscle and bone masses in the paretic limb is a prominent feature of hemiplegia and hemiparesis [1][2][3][4], because of longstanding disuse of the affected side [5][6][7][8]. Muscle wasting in the affected side causes greater vascular resistance, due to a decrease in venule density in skeletal muscle, leading to lower muscle flow rates [9].…”
Section: Introductionmentioning
confidence: 99%